2002
DOI: 10.1002/ptr.835
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the toxicological effects of Catha edulis leaves: a short term study in animals

Abstract: In this study the short term (3 months) toxicological effects of varying levels of Catha edulis leaves were examined on the plasma concentration of liver enzymes and the histopathology of tissue sections of various organs including the liver, kidneys, spleen and testis. Both the biochemical and histopathological data demonstrated, initial signs of Catha edulis toxicity. Our results show a significant increase in plasma levels of alkaline phosphatase (ALP) and alanine aminotransferase (ALT) with all levels of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
81
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 5 publications
11
81
2
Order By: Relevance
“…27 It can provide a quantitative assessment of the degree of damage to the liver. 28 Our results show that ETDE caused no damage to the liver as shown Sucheta et al 29 Urea and creatinine are markers of renal function 25 have not seen their rates varied by ETDE.…”
Section: Discussionsupporting
confidence: 62%
“…27 It can provide a quantitative assessment of the degree of damage to the liver. 28 Our results show that ETDE caused no damage to the liver as shown Sucheta et al 29 Urea and creatinine are markers of renal function 25 have not seen their rates varied by ETDE.…”
Section: Discussionsupporting
confidence: 62%
“…In rats, a decreased serum level of free radical metabolising/ scavenging enzymes and glucose has been observed after oral administration, suggesting a deranged systemic capacity to handle oxidative radicals after khat use (Al-Qirim et al, 2002). It has also been reported that khat induces cytotoxic effects in cells (Al-Ahdal et al, 1988;Al-Meshal et al, 1991;Al-Mamary et al, 2002;Dimba et al, 2003) and in lymphoid tissue, and in the liver and kidney after per oral administration to white rabbits (Al-Meshal et al, 1991;Al-Mamary et al, 2002), but the mode of cell death has not so far been addressed.…”
mentioning
confidence: 99%
“…The hepatotoxic features from these studies revealed marked increases in the plasma concentrations of alkaline phosphatase and liver transaminases, along with steady increases in direct and total bilirubin levels. Additionally, histopathological analysis from these studies revealed mixed inflammatory infiltrate and portoportal fibrosis [7,8]. Human studies have corroborated this evidence through an increasing number of case studies published from Europe and Australia on khat-induced hepatotoxicity in Yemeni and Somali immigrants [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 75%
“…With khat use becoming more prevalent, there has been an increased awareness and growing concern about the potential for khat-induced hepatotoxic injury [1,[6][7][8][9][10][11][12][13]. Animal studies published in 2002 have evaluated the toxicological effects of long-term khat ingestion and have shown significant hepatotoxic injury from khat exposure in rabbits [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation